Using the Multisensory Teaching Approach in Early Childhood Education: Educators’ Perspectives - Lupiya Mpolomoka, Daniel (Journal of Early Childhood Development and Education, 2025)
Background of Study: Multisensory teaching has gained recognition as an effective strategy in early childhood education by engaging visual, auditory, kinesthetic, and tactile modalities. These approaches improve engagement, cognitive development, and retention of knowledge. However, implementation is often limited by challenges such as insufficient resources, large class sizes, and inadequate teacher training. Aims and Scope of Paper: This paper explores educators’ perspectives on the application, benefits, and barriers of multisensory teaching methods in early learning environments, with particular attention to their role in fostering inclusive education. Methods: The study employed a qualitative design, collecting data through interviews, focus group discussions, and classroom observations with early childhood educators. Result: Findings show that multisensory teaching, including storytelling, music, movement, sensory play, and hands-on activities, enhances children’s participation, cognitive growth, and knowledge retention. Educators emphasized its value for learners with diverse needs. Nonetheless, they identified challenges such as limited training opportunities, overcrowded classrooms, and resource shortages that hinder consistent implementation. Conclusion: The study concludes that multisensory teaching offers significant potential for improving early childhood education. Greater institutional support, professional development, curriculum integration, and policy-level investment are needed to optimize its benefits and promote inclusive, effective learning experiences.